Peer pressure and parenting styles as predictors of gambling behaviour among adolescents in selected secondary school - Babatunde, Stephen Ishola; Adeleke, Oladele Adelere; Egwuonwu, Davis Ifeanyi; Adenike, Adebimpe Oluwafisayo; Adekoya, Oluwatomisin Rebecca (Journal of Indonesian Psychological Science (JIPS), 2025)
This study examined the predictive influence of peer pressure and parenting styles on gambling behaviour among adolescents in selected secondary schools in the Ijebu North Local Government Area of Ogun State, Nigeria. A descriptive survey research design was adopted, involving 200 in-school adolescents randomly selected from four secondary schools located in Ijebu-Igbo, Oru, Awa-Ilaporu, and Ago-Iwoye. Data were collected using a structured instrument titled Peer Pressure and Parenting Styles as Predictors of Gambling Behaviour among Adolescents Questionnaire (PPSPGBQ). Content validity was established by experts in clinical psychology, while reliability analysis yielded Cronbach’s alpha coefficients of 0.86, 0.93, and 0.94, indicating strong internal consistency. Descriptive and inferential statistical analyses were conducted to test the study hypotheses. Findings revealed that peer pressure significantly predicted gambling behaviour among adolescents, and that peer pressure and parenting styles jointly predicted gambling behaviour. Peer pressure emerged as the stronger predictor of gambling tendencies. The study underscores the need for targeted preventive strategies, including workshops, seminars, and school-based interventions, to mitigate the growing risk of gambling among adolescents